Locality-dependent descending reflex motor activity in the anal canal–cholinergic and nitrergic contributions in the rat model - Radomirov Radomir; Ivancheva Christina; Itzev Dimitar; Petkova-Kirova Polina (Acta Pharmacologica Sinica, 2016)
Aim: Since the distal part of the intestine is targeted by a wide range of pathogens, the motility of the recto-anal region has been the object of many experimental and clinical observations. In this study, we investigated descending motor responses in the anal canal as a measure of the activation of autonomic reflex pathways underlying evacuatory recto-anal activity. Methods: The partitioned organ bath method was used to register motor responses of the anal canal as induced by balloon distension of the rectum in isolated rat recto-anal preparations. Results: Distension-induced descending responses of the anal canal comprised contractions (with distension at a distance of 15 mm), initial contractions and secondary relaxations (at 10 mm) and short contractions followed by deep relaxations (at 3−5 mm). Decreasing the distance between the distension stimulus and the anal canal resulted in a decreased contraction response and increased relaxation. Tetrodotoxin (0.1 μmol/L) inhibited these responses. Atropine (0.3 μmol/L) decreased contraction and did not change the relaxation response. NG-nitro-L-arginine (0.5 mmol/L) enhanced contraction in both the absence and presence of atropine. L-arginine (0.5 mmol/L) inhibited contraction and extended relaxation in atropine-pretreated preparations. The actions of NG-nitro-L-arginine and L-arginine were more pronounced in the aboral direction. ChAT-positive nerve fibers were observed in myenteric ganglia of the rectum and the anal canal. The density of NADPH-diaphorase-positive neurons was higher in the anal canal region. Conclusion: Our results suggest that locality-dependent activation of the descending reflex neuromuscular communications underlie evacuatory activity in the recto-anal region. This activation response involves long excitatory cholinergic and non-cholinergic pathways along the rectum and short inhibitory nitrergic pathways located predominantly in the anal canal region.